Electrophysiological and Pharmacological Characteristics of Triggered Activity Elicited in Guinea-Pig Pulmonary Vein Myocardium - Akira Takahara; Takahiko Sugimoto; Takuma Kitamura; Kiyoshi Takeda; Yayoi Tsuneoka; Iyuki Namekata; Hikaru Tanaka (Elsevier, 2011)
The pulmonary vein is known as an important source of ectopic beats, initiating frequent paroxysms of atrial fibrillation. We analyzed electrophysiological and pharmacological characteristics of triggered activity elicited in the isolated pulmonary vein from the guinea pig. Immediately after the termination of train stimulation (pacing cycle length of 100 ms), spontaneous activities accompanied with phase-4 depolarization were detected in 43 out of 45 pulmonary vein preparations. Such triggered activities were not observed in the isolated left atrium. The incidence of triggered activity was higher at a shorter pacing cycle length (100 - 200 ms), and the coupling interval was shorter at a shorter pacing cycle length. Verapamil (1 μM), ryanodine (0.1 μM), and pilsicainide (10 μM) suppressed the occurrence of triggered activities. The resting membrane potential of the pulmonary vein myocardium was more positive than that of the left atrium. Carbachol (0.3 μM) hyperpolarized the resting membrane potential and completely inhibited the occurrence of triggered activities. These results suggest that the pulmonary veins have more arrhythmogenic features than the left atrium, possibly through lower resting membrane potential. The electrophysiological and pharmacological characteristics of triggered activity elicited in the pulmonary vein myocardium were similar to those previously reported using ventricular tissues. Keywords:: triggered activity, pulmonary vein, left atrium, membrane potential, carbachol